1992
DOI: 10.1038/sj.bdj.4807956
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary report on the effect of storage in water on the properties of commercial light-cured glass-ionomer cements

Abstract: Two commercially available light-curable glass-ionomer cements, Vitrebond and XR-Ionomer, have been studied and their compressive strengths measured following storage under wet and dry conditions for varying lengths of time up to 3 months. The strongest cements were those stored in air and allowed to age. On the other hand, cements that were stored in water were found to become progressively weaker with time. Their failure mode was different from that of cements stored in air in that specimens became barrel-sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
38
0
6

Year Published

1994
1994
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(47 citation statements)
references
References 0 publications
3
38
0
6
Order By: Relevance
“…While some studies have reported negative effects on physical properties as a result of water storage and subsequent sorption 17,[19][20][21][22][23][24][25][26] , Mitra 10) has found no significant differences in properties immediately after curing and extended storage in water. In our study, the hydration properties of conventional glass-ionomer cement and its hybrid versions were also investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While some studies have reported negative effects on physical properties as a result of water storage and subsequent sorption 17,[19][20][21][22][23][24][25][26] , Mitra 10) has found no significant differences in properties immediately after curing and extended storage in water. In our study, the hydration properties of conventional glass-ionomer cement and its hybrid versions were also investigated.…”
Section: Discussionmentioning
confidence: 99%
“…These results were consistent with those of the present study. It is noteworthy that both water uptake and water loss of restorative materials can compromise the physical properties of restorations 17,[19][20][21][22][23][24] . If water is lost due to desiccation, the reactions may stop and surface crazing may occur 19) .…”
Section: Discussionmentioning
confidence: 99%
“…This could be attributed to an increase in the rigidity of the cement matrix, whereby water molecules were discharged from the cement structure. Similarly, Nicholson et al and Saygili et al reported an increase in the compressive strength of conventional glass ionomer cements under dry condition 22,23) . The compressive strength of cylindrical specimens is known to be related to the sum of shear and tensile stresses raised in the specimen body under a compressive load 24,25) .…”
Section: Discussionmentioning
confidence: 99%
“…Metal ion which was detached from hydroxyl compound inside hybrid ionomer cement will cause the material to be fragile. 10 hybrid ionomer cement will absorb the liquid which will dissolve matrix forming cation and anion to surrounding areas. This happening will produce fragile cement dissolved easily, causing transparent significant alteration.…”
Section: Discussionmentioning
confidence: 99%